Percobaan Tarik-Langsung pada Beton Konvensional - Han, Ay Lie; Narayudha, Moga; Sabdono, Parang (Department of Civil Engineering, Diponegoro University, 2004)
Although the tensile strength of concrete does not plays a predominant role in the analysis and design of concrete structures, the knowledge of concrete behavior under tension is of value when estimating the load level under which cracking will occur. The relation between compression and tensile strength is developed based on experimental results and is represented as a formula highly depending on the tensile testing method in the laboratories.Â The Splitting Tensile Test and Flexural Strength Method are well know, while the Direct Tensile Test is relatively young, and its acknowledgement by ASTM under process.Â The experimental research conducted at the Concrete and Structural Laboratory, Diponegoro University, Semarang tries to give a better view to the Direct Tensile Test for concrete.Â This paper presents in brief, the indirect and direct testing methods, and evaluates the data obtained.Kata kunci : Kuat tarik beton, direct Tensile test, indirect test, kuat tekan betonPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3889[How to cite: Aylie, H., Narayudha, M., dan Sabdono, P., 2004, Percobaan Tarik-Langsung pada Beton Konvensional, Jurnal Media Komunikasi Teknik Sipil, Volume 12, Nomor 3, pp. 75-83]